2008
DOI: 10.1016/j.pec.2008.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Using health communication best practices to develop a web-based provider–patient communication aid: The CONNECT™ study

Abstract: Objective-Although there is broad consensus that careful content vetting and user testing is important in the development of technology-based educational interventions, often these steps are overlooked. This paper highlights the development of a theory-guided, web-based communication aid (CONNECT™), designed to facilitate treatment decision making among patients with advanced cancer.Methods-The communication aid included an online survey, patient skills training module and an automated physician report. Develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 59 publications
1
47
0
Order By: Relevance
“…[20,21] observed that learning is a way for patients to gain some control of the situation and, thus, decreases anxiety. The 11 studies that used randomized controlled groups and the 3 studies that used cross sectional surveys report that OHE offered patients better emotional state and improved their satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…[20,21] observed that learning is a way for patients to gain some control of the situation and, thus, decreases anxiety. The 11 studies that used randomized controlled groups and the 3 studies that used cross sectional surveys report that OHE offered patients better emotional state and improved their satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…The users' needs were the main focus, as this has previously been shown to be the determining factor for the usability of the program [23,[35][36]. Users' experiences are important, but other experts, in this case physicians and nurses, are needed to evaluate the content if the users do not have experience of the context [36].…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the literature located one published study about a web-based patient communication skills module (Fleisher et al, 2008). This module, part of a larger physicianÁpatient communication intervention, was based on the PACE curriculum.…”
Section: Methods Of Trainingmentioning
confidence: 99%